IMPLEMENTASI MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM SMP NEGERI 7 KOTA TANGERANG - Eka Wahyuni; Fitriana Fitriana (Universitas Muhammadiyah Tangerang, 2021)
This research is aims to improve learning outcomes in Islamic Relegious Education subject by using Project Based Learning (PjBL) model. This type of research is qualitative with a descriptive-analytic approach. The results of this study indicate that; (1) Implementation of Project Based Learning (PjBL): The first stage is designing learning which includes studying the syllabus, identifying learning materials, determining learning objectives, determining learning strategies and learning methods, determining learning media and resources, and preparing learning instruments. The second stage is the implementation of learning based on plans that have been made previously. The learning runs smoothly with the Project Based Learning (PjBL) steps, which are fundamental questions, compiling a project plan, compiling a schedule, monitoring, testing results, and ending the evaluation of experiences. (2) The results of the application of Project Based Learning (PjBL) are to improve student learning outcomes in the subject of Islamic Religious Education, increase student enthusiasm in learning, increase student interest in learning, train students to think critically, be active, responsible, dare to express opinions, and students can respect the opinions of others. Students are trained to be confident and polite towards older people or adults, besides that students are trained to contextualize the knowledge they have. (3) the obstacle faced is the lack of student activity, because students still seem shy and lack self-confidence.